Fintech for sustainable agriculture: insights from Tamil Nadu, India - Vasudevan, Asokan; Rani, P. Jansi; Raja, N.; Nedumaran, G.; Arokiasamy, Anantha Raj A.; Qian, Cheng (Frontiers in Sustainable Food Systems, 2025)
Fintech, or financial technology, is transforming the agriculture sector by enhancing access to capital, optimizing the utilization of resources, and promoting sustainable agriculture practices. This research assesses how fintech can promote sustainable agriculture in Tamil Nadu, India, through an analysis of how it influences climatic resilience, environmental sustainability, and financial inclusion. The research examines the impacts of fintech, mobile market access platforms, and precision farming technologies on agricultural sustainability and production by surveying farmers across the region. The findings indicate that farmers can embrace green farming methods, access broader markets, and acquire loans with greater ease using fintech, reducing resource wastage and enhancing economic stability. The effectiveness of fintech solutions is, nonetheless, significantly influenced by factors such as legislative support, infrastructural availability, and digital literacy. The research stresses that for the maximum benefit to small and marginal farmers, targeted digital literacy programs and increased fintech access are needed. For policymakers, financial institutions, and stakeholders in the agricultural sector, the findings of the research make valuable recommendations on the appropriate utilization of fintech technologies to address sustainability challenges and enhance rural economic development.